2015
DOI: 10.1021/acs.energyfuels.5b00594
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tars Produced in Pyrolysis of Four Coals under Various Conditions in a Viewpoint of Radicals

Abstract: Many studies tried to correlate coal pyrolysis conditions with reactivity of tars produced, but few analyzed the radical concentration of tars. This work studies pyrolysis of four coals, with carbon contents in a range of 74−82 wt %, in a fixedbed tubular reactor at three heating rates and three N 2 -purging rates. The changes in the radical concentration of tars under various conditions, such as in solvents (hexane or tetrahydrofuran) or at high temperatures (300, 350, 400, and 450°C), are analyzed. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It must be noted that the pyrolysis product distribution depends strongly upon temperature [52]. Slow heating rates increase the amounts of volatiles and tar as well as their formation temperatures [53], indicating significant heat and mass transfer limitations during the pyrolysis process.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that the pyrolysis product distribution depends strongly upon temperature [52]. Slow heating rates increase the amounts of volatiles and tar as well as their formation temperatures [53], indicating significant heat and mass transfer limitations during the pyrolysis process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to viscosity, the free radical concentration during a chemical reaction depends on the type of solvent. There was a mention in some literature by Russell et al that the polarity, dielectric constant, and kinematic viscosities of the solvents may have an effect on specific free radical reactions for specific compounds. He et al measured the free radical content in tars when mixed with different solvents prior to pyrolysis. It was shown that the tars contained some entrapped free radicals inside macromolecules that were reportedly only released and detectable when a solvent was added.…”
Section: Introductionmentioning
confidence: 99%
“…12 The high-viscosity pitch in tar is likely to condensate and mix with coke and dust in tar, leading to frequent clogging of volatile product lines and devices and affecting the long-term stable operation of the system. 13,14 Besides, the pitch in tar is also difficult to be treated, which against the subsequent tar upgrading. 15,16 To overcome these problems, the authors' previous study proposed a novel poly-generation process, which integrated low-rank coal pyrolysis and gasication with char gasication gas as heat carrier, 17 as is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%